10년간 국내 양방 의학 학술지에 게재된 한방치료 부작용 사례 고찰 - 이명화; 손변우; 김경민; 전수형; 김영균; Lee, Myeong-hwa; Son, Byun-woo; Kim, Kyoung-min; Jeon, Soo-hyung; Kim, Young-kyun (대한한방내과학회지, 2018)
Objectives: The aim of this study was to report the current status of the Korean traditional medicine side effects described in domestic western medical journals in the past 10 years. Methods: We searched for domestic western medical papers about Korean traditional medicine side effects cases from January 1, 2008, to August 31, 2017. Results: Thirty papers were selected from 31 studies. The number of papers of side effects caused by acupuncture was 21 (70%), by herbal medication was 7 (23%) and by thread lifting was 2 (7%). The number of papers of side effects caused by Korean medical doctors was 20 (66.8%), by non-medical persons including patients was 2 (6.6%), by herbal pharmacists was 1 (3.3%), by multiple practitioners, including Korean medical doctors, was 1 (3.3%), and by unknown persons was 6 (20%). Reported side effects were mostly mild, except for death and severe side effects. Conclusions: Studies of Korean traditional medicine side effects are short, and in-depth studies of stability are needed. These studies will improve the safety of the Korean traditional medicine.